Amorphous metal boride as a novel platform for acetylcholinesterase biosensor development and detection of organophosphate pesticides. (30th November 2018) - Lu, Xiong; Li, Yanshan; Tao, Lu; Song, Dandan; Wang, Yuanzhe; Li, Yan; Gao, Faming
Abstract: The exploration of new materials for modifying electrodes is important to advance electrochemical biosensors. Herein, we demonstrated that amorphous bimetallic boride material (Co–2Ni–B) prepared by a simple and facile aqueous reaction is an efficient matrix to immobilize acetylcholinesterase (AChE) to construct a biosensor for the determination of organophosphate pesticides. The effects of different composition and crystallinity on its electrochemical performance are investigated, and the optimization studies of the biological transducer were also discussed. Under optimal conditions, the fabricated sensor showed good analytical performance for the determination of chlorpyrifos with a low limit of detection (2.83 pM) and a wide linear range (3 pM–300 nM). The proposed biosensor also demonstrated high reproducibility, stability and accuracy. The impressive performance was due to the excellent conductivity and the unique amorphous bimetal–metalloid complex nanostructure. These results introduce a new class of promising materials as a robust platform for biosensor applications.